Tunability of guest release properties and crystal structures in a supramolecular benzothiophene heterocyclic host complex1. Issue 16 (28th April 2015) - Wakabayashi, Takashi; Kitamura, Sayaka; Tabata, Hideyuki; Kuroda, Reiko; Imai, Yoshitane
<x xml:space="preserve">Abstract</x> A supramolecular benzothiophene heterocyclic host complex was successfully prepared by combining benzo[b]thiophene-3-acetic acid and chiral (1R, 2S)-2-amino-1, 2-diphenylethanol.